THE IMPLEMENTATION OF LEARNING DEVICES WITH SCIENTIFIC APPROACH TO IMPROVE STUDENT LIFE SKILLS (Department of Physics, Faculty of Mathematics and Natural Sciences, 2017)
The purpose of this study was to test the effectiveness of the implementation of learning device with scientific approach to improve student life skills. The research uses one group pre test–post test design. Subjects in this study were students of grade ten (class X). Implementation of learning device supports effectively in learning activities if the implementation of a lesson plan by teachers, student social skills and student academic skills at least in a good category. The results showed that the implementation of lesson plan by teachers to get the average value of 3.38 are in the very good category, gain value of the student social skill at average value of 3.03 is in the very good category, and gain of student academic skill at average value of 76 is in the good category. It concludes that the implementation of learning tools with scientific approach support effectively in learning activities.